Building a Case for Responsible Management Education in Nepal - Shrestha, Anup (Apex Journal of Business and Management, 2023)
There is a need for substantial management development, which is a precondition for Nepal's social and economic transformation. Responsible management education can play a crucial role in this transformation, and the Six Principles of Responsible Management Education (PRME) can guide business schools in the development of responsible management education. However, there are specific challenges faced in advancing responsible management education in Nepal. These challenges include the perceived identity of the higher education sector in Nepal, capacity development for management educators, and the need for country-specific teaching resources. The education sector in Nepal needs to prepare skilled human resources necessary to achieve its vision of "rebuilding a resilient nation, promoting entrepreneurial spirit, and creating a knowledge-based society". Responsible management education can contribute to this vision by promoting sustainable development and social transformation. There is a need to examine its impact on the quality of education. The COVID-19 pandemic has also impacted the education system in Nepal, highlighting the need for sustainable solutions to manage the crisis and build a resilient education system. In conclusion, responsible management education is crucial for Nepal's social and economic development. The Six Principles of Responsible Management Education can guide business schools in the development of responsible management education. However, there are specific challenges faced in advancing responsible management education in Nepal, which require a concerted effort from all stakeholders to address. responsible management education should be incorporated.